Benefits of starting hypothermia treatment within 6 h vs. 6-12 h in newborns with moderate neonatal hypoxic-ischemic encephalopathy - Wen Jia; Xiaoping Lei; Wenbin Dong; Qingping Li (BMC, 2018)
Abstract Background It has been suggested that mild hypothermia treatment of hypoxia-ischemic encephalopathy (HIE) should start within 6 h after HIE, but many children are admitted to the hospital > 6 h, particularly in developing areas. We aimed to determine whether hypothermia treatment could remain effective within 12 h after birth. Methods According to their admission, 152 newborns were enrolled in the < 6 h and 6-12 h after HIE groups. All newborns received conventional treatment combined with mild head hypothermia therapy, according to our routine clinical practice. Some newborns only received conventional treatment (lacking informed consent). All newborns received amplitude-integrated electroencephalography (aEEG) monitoring for 4 h and neuron-specific enolase (NSE) measurement before and after 3 days of therapy. Results Compared to the conventional treatment, hypothermia significantly improved the aEEG scores and NSE values in all newborns of the < 6-h group. In the 6-12-h group, the aEEG scores (F = 5.67, P < 0.05) and NSE values (F = 4.98, P < 0.05) were only improved in newborns with moderate HIE. Hypothermia treatment seems to have no effect in newborns with severe HIE after 6 h (P > 0.05). Hypothermia improved the rates of neonatal death and 18-month disability (all P < 0.01). Conclusions In newborns with moderate HIE, starting hypothermia therapy < 6 h and 6-12 h after HIE showed curative effects. In those with severe HIE, only starting hypothermia therapy within 6 h showed curative effects.